The impact of the microbiome in cancer: Targeting metabolism of cancer cells and host - Huang, Jia-Ting; Mao, Yu-Qin (Frontiers in Oncology, 2022)
Abnormal metabolic alterations of cancer cells and the host play critical roles in the occurrence and development of tumors. Targeting cancer cells and host metabolism can provide novel diagnosis indicators and intervention targets for tumors. In recent years, it has been found that gut microbiota is involved in the metabolism of the host and cancer cells. Increasingly, gut microbiome and their metabolites have been demonstrated great influence on the tumor formation, prognosis and treatment. Specific gut microbial composition and metabolites are associated with the status of tumor in the host. Interventions on the gut microbiota can exert the protective effects on the tumor, through the manipulation of structure and its related metabolites. This may be the new approach to improve the efficacy of tumor prevention and treatment. Here, we discuss the effects and the underlying mechanisms of gut microbiota and microbial-derived metabolites in tumor progression and treatment.